Internet of Things in Srilankan Hospitals : A Critical Evaluation of the Role of Social Moderators (Global Journal of Management and Business Research, 2020)
The globalization of healthcare enables us with the lens to look at the future through the economical globalization of the country and as the infrastructure for a better mankind. Healthcare in modern era is more of a system that connects health technologies, services and application provided to public health. The smart rehabilitation based on Internet of Things (IoT) was introduced very recently mainly to overcome issues of scarce resource caused by growing aging population. On the other hand, shortage of doctors is a much critical issue where the crowded hospitals and long waiting list to seek doctors as well as less time spend for consultation are because of mal distribution of doctors. This study attempted to evaluate the impact of the technological acceptance determinants on adoption towards IoT in the healthcare system and evaluate the moderating effect of provincial area as well as demographic factors in adoption towards IoT in the Srilankan hospitals.
Keywords: internet of things; hospital; mhealth; UTAUT; adoption